2004
DOI: 10.1093/bja/aeh063
|View full text |Cite
|
Sign up to set email alerts
|

Puerperal uterine inversion and shock

Abstract: Uterine inversion is an unusual and potentially life-threatening event occurring in the third stage of labour. It is associated with significant blood loss, and shock, which may be out of proportion to the haemorrhage, although this is questionable. When managed promptly and aggressively, uterine inversion can result in minimal maternal morbidity and mortality. A recent case is described, followed by a short review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 6 publications
1
37
0
4
Order By: Relevance
“…3 Factors associated with uterine inversion include short umbilical cord, excessive traction on the umbilical cord, fundal implantation of the placenta, antepartum use of magnesium sulphate, administration of oxytocin, umbilical cord traction with vigorous fundal pressure, especially in cases of a fundal placenta, rapid and long labour, and previous uterine inversion. [4][5][6] It is also more frequent in primipara and in women previously delivered by caesarean section. The diagnosis of the puerperal uterine inversion is mainly clinical.…”
Section: Discussionmentioning
confidence: 99%
“…3 Factors associated with uterine inversion include short umbilical cord, excessive traction on the umbilical cord, fundal implantation of the placenta, antepartum use of magnesium sulphate, administration of oxytocin, umbilical cord traction with vigorous fundal pressure, especially in cases of a fundal placenta, rapid and long labour, and previous uterine inversion. [4][5][6] It is also more frequent in primipara and in women previously delivered by caesarean section. The diagnosis of the puerperal uterine inversion is mainly clinical.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that quick replacement of the inverted uterus and resuscitation will give a better outcome [10]. The early involvement of a senior Obstetrician and multi-disciplinary Obstetric emergency team, is very vital.…”
Section: Discussionmentioning
confidence: 99%
“…If correction is not obtained with tocolytic agents, general anaesthesia with halothane may be induced to provide uterine relaxation. This approach may be specially useful when the woman is haemodynamically unstable, because halothane anaesthesia has fewer potential adverse effects on haemodynamics [17,20]. About this concern, it is interesting to note here that epidural analgesia does not help in uterine reposition, as it does not affect uterine tone [21].…”
Section: Treatmentmentioning
confidence: 98%
“…Haemorrhage is the most frequent symptom and shock seems to be secondary to the blood loss and neurological response to the pelvic ligamentarial traction [17]. Occasionally, when time permits and equipment is urgently available, sonography may help in diagnosis.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation